Finanční deriváty jako finanční instrumenty a hazard - Makovský, Zdeněk; Tetřevová, Liběna (Univerzita Pardubice, 2007)
The article deals with the problems of financial derivatives in connection with financial instruments and hazard. Firstly, alternative reasons of using financial derivatives are explained. Then, financial derivatives as financial instruments are characterized. At the end of the article the attention is paid to the financial derivatives as gambling.
Keywords: financial derivatives; financial instruments; hazard; Risk; hedging; trading